Lactose Intolerance in Sub-Saharan Africa (Nigerian Journal of Physiological Sciences, 2025)
Lactose is a disaccharide mainly found in dairy and dairy-containing products which yields D-galactose and D-glucose on hydrolysis. Lactose intolerance (LI) is characterized by abdominal pain, bloating, flatulence, nausea and/or diarrhoea following ingestion of dairy or lactose-containing meals. LI affects about 75% of the world’s population though the condition is poorly recognized despite being of great public health significance in sub-saharan Africa (ssA). The aim of the review is to highlight the epidemiology, types, pathophysiology, genetics, diagnosis, management and prevention of LI. Literature search was performed using Pubmed, Crossref and Google Scholar databases for the terms "lactose," "lactose consumption," "lactose intolerance," and "sub-saharan Africa." The high prevalence of LI in most countries of ssA is a major cause for concern with malnutrition as an independent entity serving as a key contributor, especially among children. Differential diagnosis for LI poses a huge challenge due to disparity in presentation of symptoms among individuals and unavailability of testing in most routine laboratories in ssA. Though wide variation in prevalence of LI exists between countries and regions within ssA, recognizing regional patterns of LI is important to guide prevention, diagnosis and management of the condition. There is also a need for increased laboratory vigilance and preparedness to tackle the silent epidemic, especially in ssA.